Net impact implementation application development life-cycle management in banking sector - Noviana Pramitasari; Yova Ruldeviyani; Irvan Ramadhan Zarkasie (Institute of Advanced Engineering and Science, 2023)
Digital transformation in the banking sector creates a lot of demand for application development, either new development or application enhancement. Continuous demand for reimagining, revamping, and running applications reliably needs to be supported by collaboration tools. Several big banks in Indonesia use Atlassian products, including Jira, Confluence, Bamboo, Bitbucket, and Crowd, to support strategic company projects. We need to measure the net impact of application development life-cycle management (ADLM) as a collaboration tool. Using the deLone and McLean model, process questionnaire data from banks in Indonesia that use ADLM. Processing data using structural equation modeling (SEM), multiple variables are analyzed statistically to establish, estimate, and test the causation model. The conclusions highlight that system quality strongly affected only User Satisfaction (p=0.049 and β=0.39). Information quality strongly affected use (p=0.001 and β=0.84) and strongly affected user satisfaction (p=0.169 and β=0.28). Service quality strongly affected only use (p=0.127 and β=0.31). Conclusion research verifies the information system's achievement approach described by DeLone and McLean. Importantly, it was discovered that system usability and quality were key indicators of ADLM success. To fulfill their objective, ADLM must be developed in a way that is simple to use, adaptable, and functional.